Role of leptin in the induction of obesity-related inflammation and infection susceptibility - Dib, Lea H. (Kansas State University, 2011)
Obesity is a metabolic disease accompanied by a disruption in the immune system leading to systemic inflammation and susceptibility to infections. Leptin, the peptide secreted by adipocytes in proportion to fat mass, is primarily a metabolic hormone translating the body’s energy status to the brain. Leptin is also a pro-inflammatory cytokine and leptin deficiency is associated with higher infection susceptibility and a protection against autoimmune diseases. Leptin’s dual metabolic-immune function places this hormone as the link between metabolic disturbances of obesity and the immune system. In the following research projects, the contribution of leptin to both inflammation and infection susceptibility was investigated in a murine model of diet-induced obesity. Chimeric mice with leptin receptor-deficient bone marrow were resistant to HFD-induced weight and fat mass gain. These mice exhibited less inflammation in the adipose tissue demonstrated by a blunted increase in tnfa and il6 gene transcript levels, a higher prevalence of anti-inflammatory macrophages and a lower number of crown-like structures. Systemically, these mice showed a tendency towards higher insulin sensitivity. These outcomes were compared to those from mice with wild-type bone marrow. Obese and lean mice exhibited similar kinetics of bacterial clearance and systemic leptin changes following infection with Ehrlichia chaffeensis in vivo. Nevertheless, isolated “obese” peritoneal macrophages were significantly less phagocytic than macrophages from lean mice and supplementation with leptin significantly increased the obese macrophages' phagocytic activity with no effect on lean macrophages. A cell line, DB-1, derived from leptin receptor-deficient bone marrow was immortalized and characterized. This cell line has phenotypic and functional properties characteristic of macrophages, lacks the long isoform of the leptin receptor, and is unresponsive to leptin. The data from the above mentioned studies suggest that leptin contributes to the inflammation of obesity. They also suggest that leptin affects macrophage function in obesity in vitro though more studies are required to assess leptin’s contribution to infection outcomes in vivo. Finally, DB-1 cells provide a dependable tool to study further the role of leptin in obesity-associated inflammation and immune system dysregulation.
Keywords: Obesity; Inflammation; Macrophages; Leptin; Infection; Immunology (0982); Molecular Biology (0307); Nutrition (0570)